2022
DOI: 10.1007/s00467-022-05455-y
|View full text |Cite
|
Sign up to set email alerts
|

Widespread kidney anomalies in children with Down syndrome

Lavinia Postolache,
Afshin Parsa,
Paolo Simoni
et al.

Abstract: Background Rare autopsy studies have described smaller kidneys as well as urinary tract anomalies in Down syndrome. This observation has never been investigated in vivo and little is known about the possible consequences upon kidney function.Here we wish to confirm whether children with Down syndrome have smaller kidneys and to evaluate their kidney function in vivo. Methods This retrospective cohort study enrolled 49 children with Down syndrome, as well as 49 age-and sex-matched controls at the Queen Fabiola … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…A small study in Japan revealed that kidney function in children with Down syndrome is 80% of average Japanese children their age suggesting that children with Down syndrome have less effective kidneys due to less functioning gromeruli or smaller kidneys [5]. Another retrospective cohort study conducted in Belgium showed similar results regarding kidney size and function with an estimated glomerular filtration rate that was decreased compared to normal limits (42%), with 14% having undiagnosed renal or urinary tract anomalies which may have contributed to their kidney function status [6]. Regarding malnutrition and decreased oral intake, a questionnaire administered to 47 normal developing children and 17 children with Down syndrome showed that children with Down syndrome tend to have more feeding difficulties [7], putting them at risk for dehydration and associated electrolyte abnormalities.…”
Section: Introductionmentioning
confidence: 93%
“…A small study in Japan revealed that kidney function in children with Down syndrome is 80% of average Japanese children their age suggesting that children with Down syndrome have less effective kidneys due to less functioning gromeruli or smaller kidneys [5]. Another retrospective cohort study conducted in Belgium showed similar results regarding kidney size and function with an estimated glomerular filtration rate that was decreased compared to normal limits (42%), with 14% having undiagnosed renal or urinary tract anomalies which may have contributed to their kidney function status [6]. Regarding malnutrition and decreased oral intake, a questionnaire administered to 47 normal developing children and 17 children with Down syndrome showed that children with Down syndrome tend to have more feeding difficulties [7], putting them at risk for dehydration and associated electrolyte abnormalities.…”
Section: Introductionmentioning
confidence: 93%
“…The spectrum of CAKUT prevalent in patients with chromosomal abnormalities is well established, with vesicoureteral reflux and lower urinary tract obstruction being predominant [ 10 ]. In addition to CAKUT, a recent report revealed that children with Down syndrome have smaller kidneys and decreased glomerular filtration rate compared to age-matched controls [ 32 ].…”
Section: Postnatal Management By a Pediatrician Pediatric Nephrologis...mentioning
confidence: 99%
“…DS patients exhibit several congenital renal abnormalities that increase susceptibility to long-term kidney disease [5]. Compared to age-matched controls, children with DS exhibit significantly smaller kidney size as well as evidence of impaired renal function [6].…”
Section: Introductionmentioning
confidence: 99%
“…DS patients exhibit several congenital renal abnormalities that increase susceptibility to long-term kidney disease [ 5 ]. Compared to age-matched controls, children with DS exhibit significantly smaller kidney size as well as evidence of impaired renal function [ 6 ]. While historically thought to be at low risk for kidney disease, research now suggests nephropathy and other renal/urinary tract complications in DS may be under-recognized.…”
Section: Introductionmentioning
confidence: 99%